Pengaruh Penggunaan Video Pembelajaran Terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Balige T.P 2023/2024 - Krisdayanti Ritonga; Oktober Tua Aritonang; Wilson Simanjuntak; Risden Anakampun; Senida Harefa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The purpose of this research is to determine the positive and significant influence of the use of learning videos on interest in studying Christian Religious Education and Characteristics of class XI students at SMA Negeri 1 Balige T.P 2023/2024. The method used in this research is a quantitative method, with a one shot case study experimental approach. The population was all class Data was collected using observation and a questionnaire totaling 48 items, namely 22 items for variable Negeri 1 Balige T.P 2023/2024: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.549 > rtable(=0.05,n=36) = 0.329. b) Testing a significant relationship obtained a value of tcount= 3.827 > ttable(=0.05,dk=n-2=34)= 2.042. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=